Megastomach caused by a pyloric schwannoma in a young woman - Alegre Salles, Valdemir José; Azevedo Scombati, Ana Clara; Olegário Gonçalves, Cauê; Pereira Lima Fraschetti, Julia; Souza Durço Alves, Larissa (Indian Journal of Case Reports, 2024)
Schwannomas are mesenchymal tumors that are characteristically benign and slow growing, which originate from any nerve with schwann cell sheath. Here, we report the case of a 28-year-old woman patient who was diagnosed with stomach obstructive lesions causing severe gastric dilatation. She underwent distal gastrectomy and the histopathological examination of the tumor revealed one obstructive gastric schwannoma.